Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1128/jcm.01950-06
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Laboratory Screening Criteria for Herpes Simplex Virus Testing of Cerebrospinal Fluid

Abstract: Most patients with herpes simplex virus (HSV) central nervous system (CNS) infection have abnormalcerebrospinal fluid (CSF) indices. Therefore, we implemented screening criteria based on CSF values and host immune status to guide testing. All CSF samples submitted for HSV PCR analysis from January 1999 through December 2004 were included in the study. Specimens from patients with human immunodeficiency virus, a history of transplants, an age of <2 years, a CSF white blood cell count of >5 cells/mm 3 , or a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 18 publications
2
45
0
Order By: Relevance
“…Our screening criteria for HSV PCR in CSF specimens, which are stricter than those of Hanson et al (5), are very sensitive and allow a significant further reduction in laboratory workload.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Our screening criteria for HSV PCR in CSF specimens, which are stricter than those of Hanson et al (5), are very sensitive and allow a significant further reduction in laboratory workload.…”
Section: Discussionmentioning
confidence: 90%
“…Of the 268 samples rejected based on our criteria, we identified 74 (27.6%) with leukocyte counts of Ͼ5 cells/mm 3 and/or protein levels of Ͼ50 mg/dl that would have met the criteria of Hanson et al (5). Of these 74 samples, 70 (94.6%) remained available for HSV PCR analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with other studies that reported positivity rates from 2.5 to 5% for CSF in a clinical setting. 15,16 In contrast, the positivity rate was much higher for samples from skin and genital lesions (almost 50%) and also for respiratory samples (30%). When respiratory samples were further differentiated, BAL specimens as samples from the lower respiratory tract had less than half of the positivity rate of other respiratory samples, which originated from the upper respiratory tract (20% versus 50%).…”
Section: Discussionmentioning
confidence: 91%